Digital Books as Learning Media for Islamic Religious Education on Hajj and Umrah Material for Middle School Students - Adam Majid Bahrudin (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
Digital books are a transformation from printed books into digital media that can be accessed through devices such as computers, tablets, or smartphones. Digital books not only display text but can also contain multimedia elements such as images, audio, video, animations, and interactive quizzes. This makes the learning process more engaging and less monotonous. In the context of learning Hajj and Umrah material, digital books can display simulations of Hajj rituals, videos of worship in the Holy Land, and maps of Hajj and Umrah journeys, all of which can strengthen students' understanding. This study aims to explore the use of digital books as a learning medium for Islamic Religious Education (PAI) on Hajj and Umrah material at the Junior High School (SMP) level. Digital books are considered capable of overcoming the limitations of conventional learning media, which are static and less interactive. By utilizing multimedia elements such as manasik simulations, videos, prayer audio, interactive maps, and educational quizzes and games, digital books provide a more contextual, visual, and enjoyable learning experience. In addition, advantages in terms of accessibility, portability, and the ability to be adapted to students' learning styles make digital books relevant to the demands of 21st-century learning. The implementation of digital textbooks in learning was carried out through online, face-to-face, and blended learning models. Effectiveness evaluations included improvements in students' conceptual understanding, learning motivation, and digital skills. The study results indicate that digital textbooks play a significant role in improving the quality of Islamic Religious Education (PAI) learning, particularly on the topics of Hajj and Umrah, and supporting digital transformation in education.